ChemInform Abstract: One Pot Imino Diels—Alder Reaction for the Synthesis of 3‐Aryl‐3, 4‐dihydrobenzo[f]quinoline Derivatives Catalyzed by Antimony Trichloride. Issue 37 (22nd August 2013) - Maiti, Gourhari; Karmakar, Rajiv; Kayal, Utpal
Abstract The three‐component method is successful for naphthylamines (I) and (X), diesters (II) and (VI) and a series of aromatic aldehydes to produce the desired structural motifs.